Pendidikan Agama Islam Berbasis Amtsal Sebagai Implementasi Pembelajaran Bermakna (Meaningful Learning) - Musringah; Dharin, Abu (Ikatan Dai Indonesia, 2025)
Islamic Religious Education (PAI) plays a central role in shaping the character and morals of students. To achieve this goal, it will be effective to study proverbs (parables) that are widely found in the Quran and Hadith. Amtal functions not only as an illustrative medium but also as a means to internalize spiritual and ethical values. In this article, we analyze how the PAI approach based on amtsal can be applied to support meaningful learning, a learning process that emphasizes deep understanding and contextual relevance in everyday life, rather than just memorizing. The study found that through a qualitative approach and literature analysis, Amtsal can improve students' ability to criticize, reflect, and connect with reality. The analogy of the Quran that concretely describes the concept of faith, good and bad, helps students understand abstract concepts in a simpler and more easily applied way. Furthermore, this approach creates a situational and personal learning experience that is in line with constructivist theory and involves students in the learning process as active agents. The meaning of education based on this proverb is to produce a generation that not only understands religious teachings from textbooks, but also has a strong moral awareness and practices Islamic values ​​in everyday life. Therefore, service-based education is the key to building a learning ecosystem that focuses on sustainable intellectual and spiritual development.